Establishment Cost of Avocados in South Florida - Braulia De Oleo; Edward A. Evans; Jonathan H. Crane (EDIS, 2014)
A major concern for the future of the Florida avocado industry is laurel wilt disease (LW), which is caused by fungus transmitted by the ambrosia beetle. Cost-effective management of LW relies heavily on the early detection and destruction of affected trees (sanitation). While not an official recommendation, some suggest that since the beetles are less attracted to younger trees, growers might consider leaving the young orchards in production while replanting only older and less productive orchards. Since the long-term survival of the Florida avocado industry may ultimately depend on a combination of eradication, prophylactic treatment, and replanting the trees, the purpose of this article is to provide an updated guidance on the costs of establishing an avocado orchard. Information presented in this study is based on interviews with growers, orchard service companies, extension agents, and other industry personnel. It is intended as a guide only to make production decisions, prepare budgets, and investigate insurance options. A follow-up document to this one will focus on the cost and return of maintaining an orchard after it has been established. This 9-page fact sheet was written by Braulia De Oleo, Edward A. Evans, and Jonathan H. Crane, and published by the UF Department of Food and Resource Economics, October 2014.